Proximal Femoral Shortening After Cephalomedullary Nail Insertion for Intertrochanteric Fractures. Issue 6 (June 2017) - Gilat, Ron; Lubovsky, Omri; Atoun, Ehud; Debi, Ronen; Cohen, Ornit; Weil, Yoram A.
Abstract : Objective: To assess the incidence of proximal femoral shortening (PFS) and its effect on the patient outcomes when intertrochanteric fractures were treated with a cephalomedullary nail (CMN). Design: Retrospective cohort study. Settings: Level II trauma center. Patients: Forty-eight consecutive patients with OTA/AO 31-A intertrochanteric fractures. Intervention: All patients were treated with a Gamma3 CMN (Stryker, Kalamazoo, MI). Methods: PFS was assessed for abductor lever arm ( x vector), femoral height ( y vector), and overall shortening ( z vector) on anteroposterior radiographs. Fixation success and retained ambulatory capacity were noted. Results: Shortening of >5 mm of the x, y, and z vectors was evident in 18, 20, and 29 patients, respectively. Shortening of >10 mm of the x, y, and z vectors was measured in 5, 6, and 8 patients, respectively. Mean shortening of the x, y, and z vectors was 4.5, 5.5, and 7 mm, respectively. Greater PFS was found to be associated with fixation failure and inability to retain ambulatory capacity, independently ( P ⩽ 0.05 and P ⩽ 0.025, respectively). Of note, an unstable fracture pattern was not found to be associated with greater PFS. Conclusions: PFS is a common phenomenon after CMN of intertrochanteric fractures with a Gamma CMN. In addition, greater PFS seems to be associated with fixation failure and inability to retain ambulatory capacity postoperatively. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.